Analysis of factors impacting electoral integrity in Africa between 2006–2023 - Examining the association between free and fair election and rule of law - Michael Oluchi Ikoko; Dilek Latif (PLoS ONE, 2025)
Regular elections in Africa are associated with increasing democratization. However, the level of electoral integrity has sparked post-electoral violence in several African countries. Furthermore, the rise of military regimes in West Africa has interrupted the democratic process in some countries. To contribute to understanding democratization, this article explores the impact of the rule of law, electoral pluralism, and political rights on free and fair elections from 2006–2023. The study used the ordinary least squares regression and wavelet quantile on quantile granger causality to examine the predictive power of the rule of law, electoral pluralism, and political rights on free and fair elections to measure electoral integrity. The results show that the three variables predict free and fair elections at different levels. The rule of law was significant at all lower levels of free and fair elections; the rule of law and electoral pluralism were both significant at moderate and higher levels. Hence, African countries with poor electoral process democracies should establish more mechanisms towards the rule of law, and a moderate level of electoral integrity should enhance the established mechanisms.